Theoretical overview of modern concepts of stress in Germany (The Journal of Psychology and Sociology, 2017)
The article deals with the problem of building modern concept of stress. The article presents an overview of the theoretical concepts such as the stress model of salutogenesis (A. Antonovsky), the transactional model of stress (R. Lazarus), the theory of the conservation of resources (Hobfoll C.), resource-oriented approach (S.Shazer). А. Antonovvskysuggestedsalutogenesis paradigm of research. Under this model, the researcher focuses primarily on cases of people successfully overcome stressful situations, even if these cases go against the general trend, and on the search for the factors that contribute to resistance to stress. These factors can be both psychological and related social environment or the physical environment. А. Antonovvsky said about the psychological health of the person as the last position at some point in the continuum lying between mental disorder and psychological well-being. R. Lazarus puts forward the idea of indirect determination of the observed under stress reactions. According to him, between the effects of the stimulus and the response includes the intermediate variables that are psychological in nature. One of these psychological processes is a threat assessment, which is the anticipation of human potential hazardous effects of exposure to it situation. The theory of the conservation of resources (S.Hobfoll) allows you to look at the nature of stress in terms of loss or threat of loss of resources and has a functional value for explaining the occurrence of psychological stress as in individuals and in the social context, explaining the interaction of groups, communities and social systems. Steve de Shazer and Kim Berg Incоо cause a lot of case studies where significant and, more importantly, a stable effect is achieved after 1 – 3 sessions. Thus, in this article we have been considered theoretical approaches to the construction of modern programs for stress management in Germany as part of behavioral therapy, and resource-based counseling.Key words: model of salutogenesis, the transactional model of stress,the theory of the conservation of resources, resource-oriented approach.